An overview of the therapeutic potential of regenerative medicine in cutaneous wound healing. Issue 3 (6th March 2017) - Pang, Calver; Ibrahim, Amel; Bulstrode, Neil W; Ferretti, Patrizia
ABSTRACT: The global burden of disease associated with wounds is an increasingly significant public health concern. Current treatments are often expensive, time‐consuming and limited in their efficacy in chronic wounds. The challenge of overcoming current barriers associated with wound care requires innovative management techniques. Regenerative medicine is an emerging field of research that focuses on the repair, replacement or regeneration of cells, tissues or organs to restore impaired function. This article provides an overview of the pathophysiology of wound healing and reviews the latest evidence on the application of the principal components of regenerative medicine (growth factors, stem cell transplantation, biomaterials and tissue engineering) as therapeutic targets. Improved knowledge and understanding of the pathophysiology of wound healing has pointed to new therapeutic targets. Regenerative medicine has the potential to underpin the design of specific target therapies in acute and chronic wound healing. This personalised approach could eventually reduce the burden of disease associated with wound healing. Further evidence is required in the form of large animal studies and clinical trials to assess long‐term efficacy and safety of these new treatments.